Conditions of work and nursing: the transverseness of the suffering in the daily life - Soraya Maria de Medeiros; Laiane Medeiros Ribeiro; Sandra Bessa de Andrade Fernandes; Verônica Simone Dutra Veras (Universidade Federal de Goias, 2006)
This paper discuss about a master's thesis academicals work. It had as objective to analyze the suffering of nursing workers through the increase of the working hours, of the multi work or the extra scales of work, of the laboring conditions in these workers' daily lives. The research was developed in a public hospital in Natal/RN. The methodology was led by a descriptive study with a qualitative approach. The technique of information collecting was employed. The individual interviews were guided by a script with open and half-structuralized questions. The period of information collecting corresponds to the months of July and August of 2003. In the analysis of data, the transcribed interviews were organized according to the group it belonged, an exhaustive reading of the texts was realized for the grouping of informations with common characteristics. Each unity of register was being grouped according to empiric categories that arose during the process. The analysis of informations was realized based in elements of the dialectic method. The results of the research lead to: the existence of an emptiness feeling and imbrutement of the affective bows with relatives; conflicts of values concerning the relation of being/having; anxiety and stress caused by impotence feelings in daily work; the feeling of dreams capture and loss as result of the working hours accumulation; recognition of the suffering through a transversal line under the sort optics. It is concluded therefore that the increase of the working hours is bringing to the workers physical and emotional consuming, and the suffering in the daily life is a result of the precariousness of the work conditions. All these factors are generating unsatisfied workers, compromising the given assistance, as well as making it difficult the interpersonal relations into the public and private dimensions of the daily life.